The Roman Gask system fortlet of Glenbank, Perthshire - Woolliscroft, David J; Hoffmann, Birgitta (Proceedings of the Society of Antiquaries of Scotland, 2010)
A geophysical survey and excavations in 1984 and 1999 confirmed the identification of the suspected Roman Gask system fortlet of Glenbank. The site was extremely poor in finds, but there was circumstantial evidence that it belonged to the Flavian tower chain rather than the Antonine reoccupation of the Gask forts. A number of nearby ring features seen beside the Roman road from the air were investigated in an attempt to trace the Gask line farther to the south-west, but appeared to be prehistoric in nature.